1994
DOI: 10.1007/bf03258479
|View full text |Cite
|
Sign up to set email alerts
|

Elimination Kinetics of Terbinafine from Human Plasma and Tissues following Multiple-Dose Administration, and Comparison with 3 Main Metabolites

Abstract: SummaryTrough and peak concentrations as well as the elimination kinetics of the antimycotic agent terbinafine and 3 metabolites were investigated following multiple-dose administration of terbinafine 250mg daily for 4, 12 and 48 weeks. Plasma, sebum and tissues such as the stratum corneum, dermis-epidermis, hair and nails were analysed. The elimination of all compounds was multiphasic, being faster initially. Mean terminal elimination half-lives of the parent drug determined in plasma and tissues ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Because of the limited duration of blood sampling and the assay limit of quantification, a third disposition phase was not observed in these early single-dose studies. Only in subsequent multiple-dose investigations in which plasma washout kinetics were followed was a third disposition phase with a half-life of about 20 to 28 days clearly identifiable (4,13). The average t 1/2 of 17 days in the present investigation is in line with these results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Because of the limited duration of blood sampling and the assay limit of quantification, a third disposition phase was not observed in these early single-dose studies. Only in subsequent multiple-dose investigations in which plasma washout kinetics were followed was a third disposition phase with a half-life of about 20 to 28 days clearly identifiable (4,13). The average t 1/2 of 17 days in the present investigation is in line with these results.…”
Section: Discussionsupporting
confidence: 89%
“…The average t 1/2 of 17 days in the present investigation is in line with these results. It is likely that this disposition phase is governed by the slow return of terbinafine to the central plasma compartment from peripheral tissue and adipose distribution sites (13).…”
Section: Discussionmentioning
confidence: 99%
“…The slow redistribution of terbinafine from tissues is responsible for the long elimination half-life observed for this drug. Based on these pharmacokinetic characteristics, terbinafine can be expected to provide sustained protection from a relapse of fungal infections following therapy (26); these pharmacokinetic characteristics also provide a rationale for a potentially shorter treatment time (13,28,43), which may be more convenient for patients.…”
Section: Discussionmentioning
confidence: 99%
“…The large volume of distribution of terbinafine and its accumulation in peripheral tissue as well as the slow redistribution of the drug into blood are likely to significantly influence the half-life of terbinafine. Previous studies have variously reported the elimination half-life of terbinafine in humans to be 15 h (33), 26 h (27), 290 h (35), and 22 days (33,35,43). Terbinafine is extensively metabolized in the liver by oxidation or N demethylation of the three carbon atoms bound to the central nitrogen atom or of the nitrogen atom itself (2), and the metabolites lack the antimycotic activity of the parent drug (34).…”
mentioning
confidence: 99%
“…However, no studies have assessed the systemic exposure of higher-dose terbinafine treatment (Ͼ250 mg daily) or divided daily doses (every 12 h [q12h] or q8h), factors that are likely to be crucial to the utility of terbinafine in effectively treating systemic mycoses in combination with other antifungals. This paucity of pharmacokinetic data is particularly important for terbinafine due to its very long terminal elimination half-life (2 to 3 weeks [13]) and substantial accumulation in plasma over time; trough terbinafine concentrations following 250 mg once daily are known to accumulate Ͼ10-fold over 12 to 20 weeks (14), with the majority of the accumulation occurring in the first 4 weeks of therapy (13).…”
mentioning
confidence: 99%